DYNAMICS OF PERIPHERAL BLOOD CIRCULATION IN TREATMENT OF RADIAL BONE FRACTURES WITH THE METHOD OF PEROSSEOUS OSTEOSYNTHESIS - I. N. Kinash (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
To study the parameters of peripheral blood circulation of upper extremity in patients with fractures of radial bone at perosseous osteosynthesis we studied the group of patients with fractures externally fixed by apparatus with pin arrangement and the group of patients treated by apparatus of rod arrangement. Rheovasographic examination of upper extremities was performed before the surgery, the day after it, on the 7th, 14th and 21st day after the surgery. In all patients during preoperational period we revealed disturbances of blood circulation in distal parts of upper extremities of angiospastic type giving evidence of sympathicotonia. Having analized the results of clinical and rheovasographic researches in established terms of observation we were able to mark gradual improvement of arterial and venous blood flow in forearm in examined groups. In the group with rod fixation positive dynamics occurred 5-7 days earlier than in the group with pin fixation. Original method was applied, consisting in rod fixation of apparatus of external fixation. Evaluation of clinical parameters marks good results in 97 % of cases. In early postoperative period improvement of rheovasographic parameters has been marked, which says about increased blood perfusion in tissues and about normalized vessel tone.